Sfudy on influence of substrate and exposure coffosive environment on adhesion ability of a modified polyethylene lined on blasted steel substrate - Chau, Van Dinh (H. : ĐHQGHN, 2017)
This paper presents a study of the adhesion ability of a modified polyethylene (sPE) lined on blasted steel substrate. Effects of pre-treatment of the substrate surface, the exposure environments, and elevated temperature on the adhesion shength, adhesion energy was conducted. A peel analysis model was established to calculate adhesion energy (fracture energy) ofthe sPE lined on the substrate from the peel data. The dumbbell tensile test was conducted at the rate of 50 mnr/min. as similar to the rate of peel test to find out the parameters using for the model. Adhesion ability of the sPE lined on the different pre-treafinent surface substrates was investigated. The Standard specimens showed the highest peel strength-adhesion energy. The adhesion energy result (2657.5 J/mz) for the Very low roughness specimens (smooth surface) was considered to the chemical bonding energy between the rhodifier/polymer and the metal oxides/metal crossing the interface. The peel strength of lined virgin PE for these substrates was also measured. The value of 743.2 Jlm2 for the Very low roughness specimens was athibuted to chemical secondary bonding energy of the base polymer and the substrates. The Standard specimen was used for testing the effects of corrosive environment on its peel shength, adhesion energy, in which the polymer face was in contact with the 60oC conosive environment while the steel face in contact with the l5oC cycling water. For the specimens exposed to the water, the reduction of 15.04% peel strength in comparison with the initial for first 864 h exposure was found while those exposed to the HCI solution was reduced about 53.94, 35.67, and 45.06 % in comparison with the initial for the first 720 h exposure. Conosion is considered a main reason for this reduction. Chloride ion accumulated on the interface was athibuted for catalysis ofthe corrosion process. The peel strength for dried specimens was unremarkably different in comparison with that in the wet condition.